Operative groups : the Latin-American approach to group analysis - Tubert-Oklander, Juan (International library of group analysis ;, 2004)
Group therapy and other dynamic approaches to the co-ordination of groups may focus either on the individual psychodynamics or on the group-as-a-whole. In Britain, group analysis developed as a group-centred approach of both therapeutic and non-therapeutic groups, from the foundational work of S.H. Foulkes. But there has been another, independent, Latin-American school of group analysis, which originated in Argentina as a result of the work and teachings of the Swiss born Argentine psychoanalyst Enrique Pichon-Rivi+¿re. This volume is a thorough introduction to operative groups. It starts by g.